2020
DOI: 10.1111/hae.13970
|View full text |Cite
|
Sign up to set email alerts
|

The Australian experience with switching to extended half‐life factor VIII and IX concentrates: On behalf of the Australian Haemophilia Centre Directors' Organisation

Abstract: Introduction Extended half‐life (EHL) factor (F) VIII and FIX concentrates became available to selected haemophilia A (HA) and haemophilia B (HB) patients in Australia in March 2018. Aim To determine factor utilization and bleeding outcomes during the first 6 months of prophylaxis with EHL concentrates, and compare it to the last 6 months of prophylaxis with standard half‐life (SHL) concentrates. Methods A national, retrospective study was performed using data extracted from the Australian Bleeding Disorders R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 11 publications
7
39
2
Order By: Relevance
“…However, we found no statistically significant change in factor usage and costs, in contrast to other real-world data, indicating that a decrease in factor consumption is possible 14 , 17 19 , 26 . The difference in our findings could be explained by the low-dose prophylactic regimen for SHL in Austria 27 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we found no statistically significant change in factor usage and costs, in contrast to other real-world data, indicating that a decrease in factor consumption is possible 14 , 17 19 , 26 . The difference in our findings could be explained by the low-dose prophylactic regimen for SHL in Austria 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…The switch to the EHL has met the expectations based on the primary reasons for switching, as we observed a statistically significant reduction in ABR and prophylactic infusion frequency per week after switching from SHL to EHL. This was also found in other publications from high-income countries investigating rFVIII-Fc, reporting higher trough levels, lower infusion frequencies and improved bleeding outcomes 6 , 17 19 , 26 .…”
Section: Discussionsupporting
confidence: 84%
“…Other real-world studies have demonstrated a reduction in factor consumption with rFIXFc prophylaxis. 17,19,20 This study also demonstrated that rFIXFc was effective in the management of bleeds in the acute setting. One or two infusions of rFIXFc resolved 90% of acute bleeds, which is similar to that reported in the phase 3 clinical trial where 97% of bleeding episodes resolved with one or two infusions.…”
Section: Discussionsupporting
confidence: 53%
“…9 Similar ABRs have been reported in other real-world studies. 17,18,20 This improvement is multifactorial, influenced by higher trough levels achieved with rFIXFc prophylaxis and more PWSHB able to achieve effective prophylaxis. The longer prophylaxis intervals possible with rFIXFc enabled patients to consider prophylaxis who were previously only able to access episodic treatment with SHL rFIX, primarily due to poor venous access, fulfilling one of the expectations of EHL products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation